Finite element modelling of composite materials and structures - Matthews, F. L. (Woodhead Publishing series in composites science and engineering., 2000)
Finite element modelling of composite materials and structures provides an introduction to a technique which is increasingly being used as an analytical tool for composite materials. The text is presented in four parts:Part one sets the scene and reviews the fundamentals of composite materials together with the basic nature of FRP and its constituents. Two-dimensional stress-strain is covered, as is laminated plated theory and its limitations. Part two reviews the basic principles of FE analysis, starting with underlying theoretical issues and going on to show how elements are derived, a model is generated and results are processed. Part three builds on the basics of FE analysis and considers the particular issues that arise in applying finite elements to composites, especially to the layered nature of the material. Part four deals with the application of FE to FRP composites, presenting analytical models alongside FE representations. Specific issues addressed include interlaminar stresses, fracture delamination, joints and fatigue. This book is invaluable for students of materials science and engineering, and for engineers and others wishing to expand their knowledge of structural analysis. Covers important work on finite element analysis of composite material performanceBased on material developed for an MSc course at Imperial College, London, UKCovers particular problems such as holes, free edges with FE results compared with experimental data and classical analysis.